Pendidikan, Pemahaman dan Penggunaan Pembayaran Online PBB: Dengan Moderasi Generasi - Marcellina Pujiono (Perspektif Akuntansi, 2022)
The application of online LBTT payment is one of method to fulfill tax obligation. This flexible service is provided by banks in cooperation with local government. There are several factors influence the success of this payment aplication, education level, understanding, generation as moderated variables. In fact, users of this payment application increase, especially for youngergeneration in which have distinguished attitudes. Younger generation have higer curiosity to have higher education to know more about technology, especially with daily used technologies. The purpose of this paper is to know the influence of education level, understanding and factor of generation in which can weaken or strengthen taxpayer’s enthusiasm of using application of online LBTT. This paper used primary data by distributing questionnaires directly to tax payers in Salatiga city, both those who have used and have never used online payments for LBTT. Analyzed data using logistic regression tests and different tests. Result shows that education level has no influence on using application of online LBTT, understanding the application of online LBTT has positive influence, generation does not moderate education level on applying online LBTT, generation moderates understanding of application of online LBTT.